Studying Late Propagations in Code Clone Evolution Using Software Repository Mining - Hui Mui, Hsiao; Zaidman, Andy; Pinzger, Martin (Electronic Communications of the EASST, 2014)
In the code clone evolution community, the Late Propagation (LP) has been identified as one of the clone evolution patterns that can potentially lead to software defects. An LP occurs when instances of a clone pair are changed consistently, but not at the same time. The clone instance, which receives the update at a later time, might exhibit unintended behavior if the modification was a bugfix. In this paper, we present an approach to extract LPs from software repositories. Subsequently, we study LPs in four software systems, which allows us to investigate the propagation time, the clone dispersion and the effects of LPs on the software.